Computational modeling of media flow through perfusion-based bioreactors for bone tissue engineering. (December 2020) - Nokhbatolfoghahaei, Hanieh; Bohlouli, Mahboubeh; Adavi, Kazem; Paknejad, Zahrasadat; Rezai Rad, Maryam; khani, Mohammad Mehdi; Salehi-Nik, Nasim; Khojasteh, Arash
Bioreactor system has been used in bone tissue engineering in order to simulate dynamic nature of bone tissue environments. Perfusion bioreactors have been reported as the most efficient types of shear-loading bioreactor. Also, combination of forces, such as rotation plus perfusion, has been reported to enhance cell growth and osteogenic differentiation. Mathematical modeling using sophisticated infrastructure processes could be helpful and streamline the development of functional grafts by estimating and defining an effective range of bioreactor settings for better augmentation of tissue engineering. This study is aimed to conduct computational modeling for newly designed bioreactors in order to alleviate the time and material consuming for evaluating bioreactor parameters and effect of fluid flow hydrodynamics (various amounts of shear stress) on osteogenesis. Also, biological assessments were performed in order to validate similar parameters under implementing the perfusion or rotating and perfusion fluid motions in bioreactors' prototype. Finite element method was used to investigate the effect of hydrodynamic of fluid flow inside the bioreactors. The equations used in the simulation to calculate the velocity values and consequently the shear stress values include Navier–Stokes and Brinkman equations. It has been shown that rotational fluid motion in rotating and perfusion bioreactor produces more velocity and shear stress compared with perfusion bioreactor. Moreover, implementing the perfusion together with rotational force in rotating and perfusion bioreactors has been shown to have more cell proliferation and higher activity of alkaline phosphatase enzyme as well as formation of extra cellular matrix sheet, as an indicator of bone-like tissue formation.